Genetic variation in nutritional properties of African yam bean (sphenostylis stenocarpa hochst ex. A. rich. harms) accessions (2017)
The genetic variability in the mineral and proximate compositions of the seeds of 40 accessions and tubers of four accessions of African yam bean (AYB), an underutilized tuberous legume in sub-Saharan Africa, was investigated. Proximate parameters; moisture content, total ash, crude protein, crude fiber, crude fat, carbohydrate and mineral elements; calcium, phosphorous, magnesium, potassium and iron of the flours were determined according to standard methods. Highly significant differences (p< 0.001) were observed in proximate compositions of the seeds. Crude protein in the seeds ranged from 19.3% (TSs153) to 25.6% (TSs51) and 15.1% (AYB 57) to 15.9% (TSs107) in tuberous accessions. Crude protein, total ash and crude fat were the major contributors (80.2%) to variation in the proximate components of the seeds. Accessions TSs140 and TSs107 were high in crude fibre contents. Magnesium and potassium were prominent in seeds (454.2 mg, 100g-1 and 398.3 mg 100g-1) and tubers (166.7mg, 100g-1 and 1010.1 mg 100g-1) respectively. This study revealed the nutritional benefits of AYB seeds and tubers which could be used as an alternative source of protein, energy requirement and food supplement for human and livestock nutrition.